Thyroid Embryonic Anomalies Involving the Medial and Lateral Anlagen: Two Surgical Case Reports - Ferdinand Rico; John Lung (Case Reports in Surgery)
Introduction. An ectopic anomalous accessory thyroid is extremely rare. We present two related case reports. Case. A 43-year-old morbidly obese female presented with a palpable left thyroid mass. Initial impression after preoperative workup was a diffuse bilateral multinodular goiter with a left nodule suspicious for malignancy. She underwent a total thyroidectomy. On further palpation after initial excision, two masses on the left neck area were noted, dissected, and excised. In the second case, a 65-year-old female presented with a substernal exophytic mass displacing the trachea to the right after a left thyroid lobectomy 4 years ago. Cytology revealed a retained substernal thyroid. She is scheduled for a substernal thyroidectomy through a median sternotomy. Discussion. In all partial or complete thyroidectomy cases, care should be taken to palpate or to use intraoperative ultrasound (IOUS) for any extra thyroid mass. An intuitive surgical approach is needed to evaluate for possible embryologic anomalies of the thyroid. There are two thyroid anlagen that can explain ectopic aberrant anomalies: the median anlage-thyroid rest and the lateral anlage from the ultimobranchial body of the fourth pharyngeal pouch. Surgeons should keep in mind that multiple ectopic thyroid glands could be present in any thyroidectomy procedure.